2016
DOI: 10.3389/fpsyg.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Emotional Development Following Very Preterm Birth: Pathways to Psychopathology

Abstract: Very preterm birth (VPT; < 32 weeks of gestation) has been associated with an increased risk to develop cognitive and socio-emotional problems, as well as with increased vulnerability to psychiatric disorder, both with childhood and adult onset. Socio-emotional impairments that have been described in VPT individuals include diminished social competence and self-esteem, emotional dysregulation, shyness and timidity. However, the etiology of socio-emotional problems in VPT samples and their underlying mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
163
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 223 publications
(313 reference statements)
11
163
0
1
Order By: Relevance
“…These mothers’ recognition of the importance of physical contact and relationship has been validated in numerous studies of the association between positive mother-infant interactions and subsequent neurodevelopment in healthy and in premature infants. 49,50 Schore’s Regulation theory delineates many of the critical neurobiological processes that occur during mother-infant interaction, 13,51 including changes in patterns of ANS activity. In newborn infants, this stimulation of regulatory pathways occurs primarily through the day-to-day repetition of holding and feeding.…”
Section: Discussionmentioning
confidence: 99%
“…These mothers’ recognition of the importance of physical contact and relationship has been validated in numerous studies of the association between positive mother-infant interactions and subsequent neurodevelopment in healthy and in premature infants. 49,50 Schore’s Regulation theory delineates many of the critical neurobiological processes that occur during mother-infant interaction, 13,51 including changes in patterns of ANS activity. In newborn infants, this stimulation of regulatory pathways occurs primarily through the day-to-day repetition of holding and feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental trajectories after preterm birth are very heterogeneous (Yaari et al ., ). Although strong everyday functioning is reported even among VPT preschoolers (Andersson, Martin, Strand Brodd, & Almqvist, ), detrimental long‐term sequelae following extremely or very preterm birth are well documented and evidenced by a substantially heightened prevalence of attention deficit disorders, learning difficulties, and behavioural and socio‐emotional problems (Aarnoudse‐Moens et al ., ; Arpi & Ferrari, ; Eryigit‐Madzwamuse, Baumann, Jaekel, Bartmann, & Wolke, ; Johnson & Marlow, ; Johnson et al ., ; Lemola, ; Montagna & Nosarti, ). Even among MLPT children, evidence for disadvantageous long‐term consequences expands: a prolonged school career due to late school enrolment and class repetition and demand for therapeutic interventions in low‐risk preterm children (Reuner, Hassenpflug, Pietz, & Philippi, ), and less advanced cognitive functioning, more school and behaviour problems, and higher prevalence of psychiatric disorders for MLPT children and adults compared with full‐term peers (de Jong, Verhoeven, & van Baar, ; Quigley et al ., ; Vohr, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although preterm children's more frequent functional differences (e.g., motor problems) and cognitive deficits (e.g., lower IQ) predicted their peer relationship difficulties in middle childhood in one study (Heuser et al, ), lower cognitive abilities do not explain a withdrawn personality factor found in adults born preterm (Eryigit‐Madzwamuse et al, ). Thus, the mechanisms underlying the link between preterm birth and social problems are still poorly understood (Montagna & Nosarti, ; Zmyj, Witt, Weitkämper, Neumann, & Lücke, ).…”
Section: Introductionmentioning
confidence: 99%